Radiographic evaluation of knee joint space width using fixed flexion view in knees of Indian adults - Jain, Ravi Kant; Jain, Abhishek; Mahajan, Pranav (International Journal of Research in Orthopaedics, 2018)
Background: The objective of this study is to evaluate the tibiofemoral joint space width in the medial and lateral compartments of the knee using digital radiograph. The measurement of knee joint space width (JSW), in between the femur and the tibia is a way of evaluating the tibio-femoral cartilage thickness. This study is aimed at establishing normal references of joint space width for use in diagnosis and follows up of knee cartilage diseases. Methods: This study is prospective and carried on 50 subjects at SAMC & PGI, Indore, M.P. One patient refused to sign the consent and was excluded. All subjects were healthy adults with sedentary lifestyle. All subjects underwent x-ray of bilateral knee joints. The joint space width of both medial and lateral compartments of each knee was measured using the scale in the computerized software. Results: The average age in the study group was 44.59 years with male preponderance.The mean left medial and lateral joint space width was 5.34 mm±1.26 mm and 5.21 mm±1.04 mm and on right side was 5.26±1.11 mm and 5.57±1.57 mm, respectively. No statistically significant difference was found between right and left knee joint space width compartments. Conclusions: The values obtained after observing the radiographic references showed no significant gender variation in knee joint space width. But, it is seen that there is a decrease in joint space width with increasing age, which progresses towards osteoarthritis of knee.